Acral-type Malignant Acanthosis Nigricans Associated with Gastric Adenocarcinoma - Lee, Sang-Sin (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
Acanthosis nigricans is a symmetric eruption characterized by the presence of a hyperpigmented, velvety cutaneous thickening, that can develop on any part of the body, but characteristically affects the flexural areas of the body. The velvety hyperkeratotic lesions can be located on the dorsum of the hands and feet in dark-skinned people in the form of a variant of acanthosis nigricans called as acral acanthotic anomaly or acral type acanthosis nigricans. Although acanthosis nigricans is associated with malignant tumors, particularly gastric carcinoma, acral type acanthosis nigricans has never been reported to be associated with gastric adenocarcinoma. In our present study, we describe a case of 58-year-old man with acral type acanthosis nigricans and its association with carcinoma of the stomach; a marked improvement was seen in the skin condition of the patient with chemotherapy.